Empirical evidence on the causality relationship between foreign direct investment and economic growth in the developing countries - Zulkarnain Zakaria (Penerbit Universiti Kebangsaan Malaysia, 2009)
The causality relationship between economic growth and foreign direct investment has generated intense research interest. The empirical study investigates the causal relationship between economic growth and foreign direct investment in 37 developing countries in multivariate framework. The major findings are, in most cases, foreign direct investment has no effect on economic growth. The study also found little evidence that economic growth causes the inflow foreign direct investment to the developing countries.